ABIF Manager: simple reading and editing of ABIF formatted files - Beran, Pavel; Mraz, Ivan (Bioinformatics, 2015)
UNLABELLED: ABIF Manager is simple application for low-level access to ABIF formatted files. Those are produced by Data Collection software based on the data, collected from capillary sequencing machine. The application shows all the data as readable text, which can be easily edited. AVAILABILITY AND IMPLEMENTATION: The program source code and compiled executable is freely available at: https://sourceforge.net/projects/abifmanager/.
Keywords: High-Throughput Nucleotide Sequencing; Software; software; vysoce účinné nukleotidové sekvenování